Gasification of plastic waste for synthesis gas production - Dang Saebea; Pornnapat Ruengrit; Amornchai Arpornwichanop; Yaneeporn Patcharavorachot (My University, 2020)
This work presents the synthesis gas production from gasification of plastic waste, i.e. polyethylene (PE) and polypropylene (PP). The steam gasification is modeled by using AspenPlusTM simulation software. The effects of gasifier temperature and steam to feed (S/F) mass ratio were examined to determine the suitable synthesis gas mole flow rate. The simulation results showed that gasifier should be operated at 900 °C with optimal S/F mass ratio as 1.5. Considering the influence of PE/PP mass ratio, the results indicated that the PE/PP mass ratio of 100/0 or pure PE can provide the maximum synthesis gas flow rate of 21 kmol/hr and H2/CO ratio of 2.1.
Keywords: Wood gas generator; Polypropylene; Mass flow rate; Mass flow; Mass ratio; Thermochemical Biomass Conversion Processes